Exercise Leads to Better Clinical Outcomes in Those Receiving Medication Plus Cognitive Behavioral Therapy for Major Depressive Disorder - Gourgouvelis, Joanne; Yielder, Paul; Clarke, Sandra T.; Behbahani, Hushyar; Murphy, Bernadette Ann (Frontiers in Psychiatry, 2018)
Objective To investigate the effects of exercise as an add-on therapy with antidepressant medication and cognitive behavioural group therapy (CBGT) on treatment outcomes in low active major depressive disorder (MDD) patients. We explored whether exercise reduces the residual symptoms of depression, notably cognition and sleep quality, and to identify putative biochemical markers related to treatment response. Methods Sixteen low active MDD patients were recruited from a mental health day treatment program at a local hospital. Eight medicated patients performed an eight week exercise intervention in addition to CBGT, and eight medicated patients attended the CBGT only. Twenty-two low active, healthy participants with no history of mental health illness were also recruited to provide normal healthy values for comparison. Results Results showed exercise resulted greater reduction in depression symptoms (p=0.007, d=2.06), with 75% of the patients showing either a therapeutic response or complete remission of symptoms versus 25% of those who didn’t exercise. In addition, exercise was associated with greater improvements in sleep quality (p=0.046, d=1.28) and cognitive function (p=0.046, d=1.08). The exercise group also had a significant increase in plasma brain-derived neurotrophic factor (BDNF), p=0.003, d=6.46 that was associated with improvements in depression scores (p=0.002, R2 = 0.50) and sleep quality (p=0.011, R2 = 0.38). Conclusion We provide evidence that exercise as an add-on to conventional antidepressant therapies improved the efficacy of standard treatment interventions. Our results suggest that plasma BDNF levels and sleep quality appear to be good indicators of treatment response and potential biomarkers associated with the clinical recovery of MDD.